Inhibitory Control in Speech Comprehension among Dai–Han Bilingual Children - Tao, Yun; Liu, Zhi; Tempel, Tobias; Chen, Rui; Ma, Xie; Wang, Xiaoxi; Liu, Yan; Qu, Yongxia (Frontiers in Psychology, 2017)
We aimed to investigate differences in inhibitory control ability between proficient and non-proficient Dai-Han bilinguals. Two experiments used a combined stimulus-stimulus and stimulus-response compatibility paradigm for this purpose. Participants were Dai-Han bilingual primary-school students selected from a Dai-speaking town in Yunnan province, China. In Dai language interference condition, participants were asked to complete a picture category task. Results showed that the effect of attentional control for non-proficient bilinguals (NPBs) was significantly greater than that for proficient bilinguals (PBs), while the effect of response inhibition was not. This implied that a difference in inhibitory control between PBs and NPBs appeared at the attention control stage when interference by the Dai lexicon emerged. In Han language interference conditon, however, participants were also asked to complete the same task. Results showed that the effect of response inhibition for NPBs was significantly greater than that for PBs, but the effect of attentional control was not. This demonstrated that a difference in inhibitory control emerged at the response inhibition stage when interference by the Han lexicon emerged. This pattern of results is opposite to previous researches, which indicated that the difference between PBs and NPBs occurred at the response inhibition stage under L1 condition, whereas at the attentional control stage under L2 condition. Based on these, this study suggests that Dai-Han bilinguals showed a remarkable second language (L2) advantage. In addition, results showed that RTs of PBs were faster than RTs of NPBs while confounding variables (e.g., intelligence, etc.) were under control. This indicates that the inhibitory control ability of the PBs is superior to that of NPBs in this study.